The influence of L1 on the use of tense and aspect in L2 writing / Sofina binti Azmi - Sofina, Azmi (2012)
The purpose of this study is to investigate the influence of L1 on the use of tense and aspect in L2 writing. A number of thirty-three (33) L2 learners from Universiti Teknologi Mara (UiTM), Puncak Perdana, Shah Alam participated in this study. A set of adapted language history questionnaire was distributed to the respondents to obtain information on the language history of the students and to gauge the learners’ proficiency level of L2. The learners were instructed to write an essay of 250 words in order to analyze any errors on tense and aspect in L2 writing. The findings from the written work showed that the learners are having difficulties in mastering the use of L2 tense and aspect of English language. The findings also revealed the highly likely causes as to why the learners are unable to use tense and aspect in L2 correctly after years of education. The implications of this study are discussed along with recommendations for future research regarding the influence of L1 on the use of tense and aspect in L2 writing.